Rock breaking regularity of layered rock mass blasting under the influence of different resistance lines - Jianxin YU; Pengzhan MENG; Xin ZHANG; Zhenzhen LI (Meitan kexue jishu, 2024)
Layered rock is a common geological structure of underground engineering construction, drilling and blasting method construction in layered rock is manifested in poor blasting and shaping effect, serious phenomenon of over and under excavation, uneven vibration propagation and other problems. Resistance line is a key parameter affecting the effect of blasting, this study takes the minimum resistance line as a control index to study the blasting and rock breaking law of layered rock body under the influence of initial stress and joint angle. Taking the Class III surrounding rock as the geological background, the concrete specimens with different nodal parameters were prepared as the simulation material of layered rock body by layered casting method, and a series of blasting experiments under different blasting conditions were carried out, and the test process was monitored by the combination of high-speed camera, dynamic signal analysis system, and intelligent five-segment bursting tachymeter and other equipment; and the damage of layered rock body under the coupling of static geostatic load and dynamic blast load and the law of stress wave propagation were analysed by using the three-dimensional numerical simulation model of LS-DYNA. The results of the study show that: joints on the propagation of blasting stress waves have a barrier effect, changing the direction and shape of crack expansion, stress waves transmitted to the joint surface after a large amount of energy reflection phenomenon, a small amount of energy transmittance phenomenon through the joint surface, The blasting effect shows that the main cracks first penetrate along the weak faces of the joints. Blasting effect shows that the main cracks first along the weak face of the joints through, perpendicular to the direction of the joints on the side of the rock crack development is better than the back side of the cracks, on the side of the explosion of the strain strength of the rock is greater than that of the back side of the explosion; As the resistance line increases from 6 cm to 10 cm, the extent of the blast crushed zone and fissure zone produced by the blasting of the laminated rock body gradually decreases; As the resistance line increases from 6 cm to 10 cm, the range of blasting crushed area and fissure area produced by blasting of layered rock body decreases gradually, but the range of blasting cavity first increases and then decreases. When the resistance line is small, the majority of the explosion energy is dissipated in the form of gas, resulting in energy wastage. However, when the resistance line is larger, the explosive energy acts upon the interior of the rock, making it difficult to project the rock. Blasting produces the best rock breakage when the line of resistance is H = 8 cm; The effective stress on the face of the joints on the side of the explosion with the increase of the minimum line of resistance shows a trend of increasing and then decreasing, and the combined velocity shows a trend of decreasing and then increasing. The peak values of the effective stress and combined velocity on the blasting side of the joint surface change smoothly. The research results contribute to a deeper understanding of the mechanism of layered rock blasting in underground engineering.